Accelerating quantitative 13C NMR spectra using an EXtended ACquisition Time (EXACT) method. Issue 56 (22nd June 2022) - Al-Aasmi, Zahra H.; Shchukina, Alexandra; Butts, Craig P.
Abstract : Accurate quantitative 13 C NMR spectra can be accelerated by using EXACT (EXtended ACquisition Time) NMR methods which reduce Nuclear Overhauser Enhancement (NOE) during the FID. Abstract : Accurate quantitative 13 C NMR spectra can be accelerated by using EXACT (EXtended ACquisition Time) NMR methods which reduce Nuclear Overhauser Enhancement (NOE) during the FID. This allows 30–50% shorter experiment times to be used when achieving a given level of quantitative accuracy.